A study of polygonal wheel wear through a field test programme. Issue 6 (3rd June 2019) - Wu, Xingwen; Rakheja, Subhash; Wu, Huichao; Qu, Sheng; Wu, Pingbo; Dai, Huanyun; Zeng, Jing; Ahmed, A. K. W.
ABSTRACT: High magnitude impact loads caused by polygonal wear of the wheels have been associated with in-service failures of structural components of high-speed railways, although the mechanisms leading to wheels' polygonalisation is not yet fully understood. In this study, a long-term field test programme is undertaken and the data are analysed to gain better understanding of the growth in polygonal wear, and its characteristics and correlation with the axle box acceleration. The field measurements on a high-speed railway involved monitoring of wheels profiles between successive re-profiling of the wheels so as to identify the rate of growth of wear in addition to the axle box acceleration. The data suggested rapid growth in wheel wear, which could be characterised by polygonal wear of nearly 18th and 19th harmonic order. It is further shown that the magnitude of axle box acceleration increased considerably with increasing wear magnitude of the wheel.